Targeted deletion of Interleukin-3 results in asthma exacerbations - Kölle, Julia; Zimmermann, Theodor; Kiefer, Alexander; Rieker, Ralf; Xepapadaki, Paraskevi; Zundler, Sebastian; Papadopoulos, Nikolaos G.; Finotto, Susetta (iScience, 2022)
The cytokine interleukin-3 (IL-3) acts on early hematopoietic precursor cells. In humans, Treg cells secrete IL-3 and repress inflammatory cells except for basophils. The present study aims to elucidate the contribution of IL-3 in the development and the course of allergic asthma. We therefore analyzed the secretion of IL-3 in PBMCs and total blood cells in two cohorts of pre-school children with and without asthma. In a murine model of allergic asthma, we analyzed the phenotype of IL-3−/− mice compared to wild-type mice. PBMCs from asthmatic children showed increased IL-3 secretion, which directly correlated with improved lung function. IL-3−/− asthmatic mice showed increased asthmatic traits. Moreover, IL-3-deficient mice had a defect in T regulatory cells in the lung. In conclusion, IL-3 downregulation was found associated with more severe allergic asthma in pre-school children. Consistently, targeting IL-3 resulted in an induced pathophysiological response in a murine model of allergic asthma.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Biological sciences; immune response; Immunology